Inside the Gate : Sigrid Undset's Life at Bjerkebæk - Skille, Nan Bentzen (Book collections on Project MUSE., 2018)
"Inside the Gate offers readers a rare glimpse into Sigrid Undset's life at her home, Bjerkebaek now a museum and national landmark in Lillehammer, Norway. Drawing on a wealth of historical documents, Nan Bentzen Skille's lively narrative presents an intimate portrait of the Nobel Prize winner's intense emotional life and creative endeavors, with Bjerkebaek at the center of it all"--